1st International Symposium onWireless Communication Systems, 2004.
DOI: 10.1109/iswcs.2004.1407244
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional ip-based mass file delivery protocol

Abstract: In this paper we define the functions of a unidirectional IP-based file delivery protocol based on research on the past work in the area. We review several pieces of historic work on file delivery protocols and therefore provide a background to the current state of the art, FLUTE, which is being developed towards standard in Internet Engineering Task Force. We also provide a comparison of different approaches and introduce items for future work in this area. File celivery; protocol; multicast; broadcastI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In a mobile, ad hoc environment, simulation experiments show that FSR is an easy, reliable, and scalable routing solution. [4] based on research into previous work in the field, identified the functions of a unidirectional IP-based file delivery protocol. The authors study several historical works on file distribution protocols to provide context for the current state of the art, FLUTE, which is being implemented as a standard in the Internet engineering task force.…”
Section: Related Workmentioning
confidence: 99%
“…In a mobile, ad hoc environment, simulation experiments show that FSR is an easy, reliable, and scalable routing solution. [4] based on research into previous work in the field, identified the functions of a unidirectional IP-based file delivery protocol. The authors study several historical works on file distribution protocols to provide context for the current state of the art, FLUTE, which is being implemented as a standard in the Internet engineering task force.…”
Section: Related Workmentioning
confidence: 99%